Involving Older and Disabled People in Assessment of Product, Environment and Service Designs - Sims, Ruth E.; Marshall, Russell; Summerskill, Steeve J.; Case, Keith; Gyi, Diane E.; Davis, P. (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2011)
For over 10 years research has been conducted by the Design School at Loughborough University in the United Kingdom (UK) into accessibility of products, services and environments with a particular focus on the needs of older and disabled people. As part of this research a computer based tool called HADRIAN has been developed to encourage empathy between designers, planners and people who are older or who may have some form of impairment. In addition, the tool provides a means to evaluate the accessibility and inclusiveness of a design by simulating the abilities of older and disabled people and performing virtual user trials where potential barriers introduced by the proposed design can be identified and rectified before the design is implemented in the real world.The paper will present and discuss the need for this work and tool, and the importance of obtaining data directly from older and disabled people, as well as three validation trials conducted to evaluate the simulation capabilities of HADRIAN compared to real people interacting with the same tasks.